2020
DOI: 10.3389/fnins.2020.00752
|View full text |Cite
|
Sign up to set email alerts
|

Autodidacticism and Music: Do Self-Taught Musicians Exhibit the Same Auditory Processing Advantages as Formally Trained Musicians?

Abstract: Multiple studies have demonstrated that musicians have enhanced auditory processing abilities compared to non-musicians. In these studies, musicians are usually defined as having received some sort of formal music training. One issue with this definition is that there are many musicians who are self-taught. The goal of the current study was to determine if self-taught musicians exhibit different auditory enhancements as their formally trained counterparts. Three groups of participants were recruited: formally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…All melodies were presented at 70 dB SPL. The melodies were the same as the melodies from previous studies (Peretz et al, 2009; Zendel et al, 2015; Zendel & Alexander, 2020). At the end of each melody, participants were asked if they heard a ‘wrong’ note.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All melodies were presented at 70 dB SPL. The melodies were the same as the melodies from previous studies (Peretz et al, 2009; Zendel et al, 2015; Zendel & Alexander, 2020). At the end of each melody, participants were asked if they heard a ‘wrong’ note.…”
Section: Methodsmentioning
confidence: 99%
“…The peak latency of the ERAN was quantified over 16 fronto‐right electrodes (AF4, AF8, AFz, Fz, F2, F4, F6, F8, FCz, FC2, FC4, FC6, Cz, C2, C4, C6) from 100 to 400 ms. These montages were chosen so data could be compared with previous studies that have used similar paradigms (Brattico et al, 2006; Lagrois et al, 2018; Peretz et al, 2009; Vuvan et al, 2018; Zendel & Alexander, 2020; Zendel et al, 2015). The epochs were chosen based on a visual approximation of the minimum amplitude before and after the peak of interest to ensure the peak picking procedure selected the correct peak, and not the peak of a different wave that occurred before or after the peak of interest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that musicianship is associated with an enhanced ability to understand speech in noise and that musical training can improve the ability to understand speech in noise 4,5 . While most studies show a musician benefit, 4,5 some studies in younger adults failed to demonstrate a musician advantage 6–10 . Most critically, the research in older adults consistently shows a musician advantage 11–13 .…”
Section: Introductionmentioning
confidence: 99%